Houlton Band of Maliseet Indian Housing Authority Trip Report: Assessment of Mold and Moisture Conditions - Brown, Kate; Gordon, Jeff (Building Research Council. School of Architecture. College of Fine and Applied Arts. University of Illinois at Urbana-Champaign, 2004)
Kate Brown and Jeff Gordon from the Building Research Council (BRC) at the University of Illinois Urbana-Champaign conducted a site visit at the Maliseet Indian Housing Authority on January 25-28, 2004. The Maliseet Indian Housing Authority administers the housing program for the Houlton Band of Maliseet Indians of Maine. The site visit provided technical assistance to the housing authority in assessing mold and moisture conditions in housing units. This report summarizes activities and issues addressed while on site. A detailed analysis of findings and ecommendations is found in PART II: Houlton Band of Maliseet Indian Housing Authority Technical Housing Assessment Report: Examining Mold and Moisture Conditions of Homes on the Houlton Indian Reservation. Made available in DSpace on 2014-09-23T21:46:46Z (GMT). No. of bitstreams: 2 license.txt: 4922 bytes, checksum: 910b249b4beec47e7ab768910c8f966f (MD5) 1206812_2004_building_research_council_aleutian_islands_opt.pdf: 26241779 bytes, checksum: ce39f2b15a190827aded7d265ad238aa (MD5) Previous issue date: 2004 U.S. Department of Housing and Urban Development, Office of Native American Programs